2006
DOI: 10.1111/j.1742-7843.2006.pto_365.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety Pharmacology, Toxicology and Pharmacokinetic Assessment of Recombinant Human ω‐Interferon Produced from CHO‐SS Cells

Abstract: Human w-interferon (IFN-w) has been shown to be well-tolerated in man and to induce reductions of hepatitis C virus RNA levels in a series of human clinical trials. Here we provide an overview of our preclinical safety evaluation of the fully-glycosylated human IFN-w produced from CHO-SS cells that is currently being evaluated clinically. IFN-w was not associated with any biologically-relevant adverse effects in a series of 10 safety pharmacology experiments, in the Ames mutagenicity test, in the micronucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Although IFN-ω has demonstrated promising antiviral activity against some viral infections in vivo and vitro, several factors could limit its antiviral efficacy, such as poor pharmacokinetics and a short half-life [36]. PEGylation, a covalent conjugation of nontoxic polyethylene glycol (PEG), has been demonstrated to improve the plasma half-life of a therapeutic protein and decrease its proteolytic sensitivity [37].…”
Section: Strategies To Improve the Antiviral Efficiency Of Ifn-ωmentioning
confidence: 99%
“…Although IFN-ω has demonstrated promising antiviral activity against some viral infections in vivo and vitro, several factors could limit its antiviral efficacy, such as poor pharmacokinetics and a short half-life [36]. PEGylation, a covalent conjugation of nontoxic polyethylene glycol (PEG), has been demonstrated to improve the plasma half-life of a therapeutic protein and decrease its proteolytic sensitivity [37].…”
Section: Strategies To Improve the Antiviral Efficiency Of Ifn-ωmentioning
confidence: 99%
“…The antibody produced by primary and/or secondary dose affects the PK of subsequent doses during multiple administrations. In fact, it has been reported that in multiple administration of human interferon omega in cynomolgus monkeys, the PK of a subsequent dose was modulated by antibodies elicited by multiple administration (2). Therefore, to compare the PK of same proteinic drug in the same experimental animal is difficult without methodological improvements.…”
Section: Introductionmentioning
confidence: 98%
“…It induces a SVR in patients infected with hepatitis C virus genotypes 1, 2 and 3 in clinical trials [128]. IFN-ω considerably reduces the production of HBsAg, comparable to the reduction obtained by treatment with IFN-α [29].…”
Section: Hepatitismentioning
confidence: 99%